83.3k views
3 votes
3x + 2y - x + 3x - y^2
please explain
100 POINTS

User Boflynn
by
5.5k points

2 Answers

2 votes

Answer:

7x + 2y - y^2.

Explanation:

I guess you want to simplify this expression.

3x + 2y - x + 3x - y^2

First bring like terms together:

= 3x + 3x - x + 2y - y^2

= 6x - x + 2y - y^2

= 5x + 2y - y^2.

User Gtaborga
by
5.0k points
2 votes

Answer:

-y^2 +2y + 5x

Explanation:

add/subtract the numbers with the same letters

3x -x + 3x = +5x

2y

-y^2

-y^2 +2y + 5x

User Bart Mensfort
by
4.7k points